2008
DOI: 10.1111/j.1755-6686.2008.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire to Evaluate and Elucidate Patients' Perceptions of Renal Dietary Advice

Abstract: This study aims to explore the knowledge and beliefs of Chronic Kidney Disease (CKD) patients about the role of diet in their disease presentation and management. Focus Groups (FG) with nephrology and dialysis patients informed the development of a questionnaire. A sixty percent response rate was achieved (115/190) with 100 complete questionnaires available for analysis. 80 respondents said they would like to receive dietary advice as soon as they know they have renal damage. In most cases this would have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…Sutton et al . () found that people strongly valued assurance by their dietitian that current eating behaviours were not causing further health damage.…”
Section: Discussionmentioning
confidence: 99%
“…Sutton et al . () found that people strongly valued assurance by their dietitian that current eating behaviours were not causing further health damage.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the Focus Groups and the Questionnaire (Sutton et al 2008) reveal some facts that affirm and validate current practice, and others that demand serious thought as to how best to develop and integrate renal dietary advice.…”
mentioning
confidence: 88%
“…A recent study carried out on the Wessex Renal and Transplant Unit, UK was designed to explore how patients perceive the timing of such advice, particularly dietary advice, from whom and how it is presented (Sutton et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has generally been accepted that much CKD is the result of hereditary or congenital disease, obstructive conditions and primary HT In such cases, diet was not considered to have a role in either contributing to or controlling progression of CKD. However, a study which asked patients when they would like to receive renal‐related dietary advice showed that almost all patients would like the opportunity to discuss diet as soon as they knew they had kidney impairment (Sutton 2008). The current view tends to be that at such an early stage, no renal‐specific dietary changes will be needed.…”
Section: Dietary Considerations Specific To Ckdmentioning
confidence: 99%